2012
DOI: 10.1891/1946-6560.3.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Partner Abuse: Rates of Emotional Abuse and Control

Abstract: Partner abuse research over the past two decades has divided violent, threatening, or abusive phenomena into discrete areas of interest to researchers that, although distinct, are still broadly defined under the common category of “domestic abuse” or, more recently, intimate partner violence (IPV). Thus, any concerted attempt to typify the various substrata of IPV research must recognize the distinct features of each area regarding their component parts (i.e., behavioral or psychological sequelae, incidence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
105
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 195 publications
7
105
1
1
Order By: Relevance
“…Moreover, although some researchers have advocated for gender-specific interventions for IPV (e.g., Leisring, Dowd, & Rosenbaum, 2005), it remains an empirical question as to whether gender specific programming is more or less effective than gender-neutral programming. Given findings of gender symmetry in rates of physical IPV, in emotional abuse and control, and in risk factors, and because men and women in the current study overlapped on 5 of the 7 motivation categories, BIP programming may prove most effective when it is primarily gender neutral (Capaldi, Knoble, Shortt, & Kim, 2012; Careny & Barner, 2012; Desmarais, Reeves, Nicholls, Telford, & Fiebert, 2012). …”
Section: Discussionmentioning
confidence: 79%
“…Moreover, although some researchers have advocated for gender-specific interventions for IPV (e.g., Leisring, Dowd, & Rosenbaum, 2005), it remains an empirical question as to whether gender specific programming is more or less effective than gender-neutral programming. Given findings of gender symmetry in rates of physical IPV, in emotional abuse and control, and in risk factors, and because men and women in the current study overlapped on 5 of the 7 motivation categories, BIP programming may prove most effective when it is primarily gender neutral (Capaldi, Knoble, Shortt, & Kim, 2012; Careny & Barner, 2012; Desmarais, Reeves, Nicholls, Telford, & Fiebert, 2012). …”
Section: Discussionmentioning
confidence: 79%
“…Moreover, research has found female-perpetrated IPV to be qualitatively different from male-perpetrated IPV regarding particular aspects of IPV (Johnson, 1995(Johnson, , 2006(Johnson, , 2008. Indeed, research has found evidence of gender asymmetry with respect to rates of physical stalking and sexual coercion because males perpetrate these acts at significantly higher rates than females (Carney & Barner, 2012;Hamel & Russell, 2013). In addition, female victims are more likely to be physically injured than male victims and tend to be more fearful of their attackers and experience more psychological distress (Hamel & Russell, 2013;Johnson, 1995Johnson, , 2006Johnson, , 2008Straus, 2009Straus, , 2010.…”
Section: Johnson's Typology Of Intimate Partner Violencementioning
confidence: 99%
“…Straus (2004a) found that 29% of 8,666 college students in samples across 16 countries perpetrated physical partner violence against romantic partners in the past year. Physical forms of violence have received the most attention in the partner violence literature; however, experts in the field have suggested that psychological aggression toward romantic partners also warrants study (Carney & Barner, 2012;O'Leary, 1999). Psychological aggression is often a precursor to physical violence in romantic relationships (Baker & Stith, 2008;Murphy & O'Leary, 1989).…”
mentioning
confidence: 99%
“…Psychological aggression can vary in nature, but examples include shouting, calling one's partner names, swearing at one's partner, or threatening to harm one's partner (Straus, Hamby, Boney-McCoy, & Sugarman, 1996). Between 80% and 90% of college students report being victims and perpetrators of psychological aggression with similar rates across genders (Carney & Barner, 2012). …”
mentioning
confidence: 99%